Voy a responder a esta pregunta con four
ejemplos típicos, todos diferentes en la naturaleza:
Ejemplo 1:
Demostrar por inducción que $n^3-n+3$ es divisible por $3$ $\forall \space n \in \mathbb{N^+}$.
Para la prueba por inducción; estas son las $\color{red}{\mathrm{three}}$ pasos para llevar a cabo:
Paso 1: Caso Base: Para $n=1 \implies n^3-n+3= 1^3-1+3=3$ que es divisible por $3$. Tal declaración tiene por $n=1$.
Paso 2: Inductivo Asunción: Asumir la afirmación es verdadera para $n=k$ tal que $n^3-n+3=\color{blue}{(k^3-k+3)}=\color{blue}{3p} \tag{1}$ Donde $p,k \in \mathbb{N^+}$.
Paso 3: Probar la Declaración tiene por $n=k+1$ tal que $$n^3-n+3=(k+1)^3-(k+1)+3$$
$$=k^3+3k^2+3k+1-k-1+3=3k^2+3k+\color{blue}{(k^3-k+3)}= 3(k^2+k)+\color{blue}{3p}=\color{#180}{3}(k^2+k+p)$$ using our inductive assumption $(1)$ the resulting expression clearly is divisible by $3$.
Hence $n^3-n+3$ is divisible by $3$ $\forall espacio \n \in \mathbb{N^+}$
QED.
(QED is an abbreviation of the Latin words "Quod Erat Demonstrandum" which loosely translated means "that which was to be demonstrated". It is usually placed at the end of a mathematical proof to indicate that the proof is complete). Alternatively, you can use $\fbox{}$
Example 2:
Use trigonometric identities and induction to prove that
$\left(\begin{array}{cc}
\cos \theta & -\sin \theta \\
\sin \theta & \cos \theta
\end{array} \right)^{n} =
\left(\begin{array}{cc}
\cos (n \theta) & -\sin (n\theta)\\
\sin (n \theta) & \cos (n \theta)
\end{array} \right)$
As before, for proof by induction; these are the $\color{red}{\mathrm{tres}}$ steps to carry out:
Step 1: Basis Case: For $n=1 \implica$ LHS
$=\left(\begin{array}{cc}
\cos \theta & -\sin \theta \\
\sin \theta & \cos \theta
\end{array} \right)^{n}$
$=\left(\begin{array}{cc}
\cos \theta & -\sin \theta \\
\sin \theta & \cos \theta
\end{array} \right)^{1}$
$=\a la izquierda(\begin{array}{cc}
\cos (1 \theta) & -\sin (1\theta)\\
\sin (1 \theta) & \cos (1 \theta)
\end{array} \right)$
$=\left(\begin{array}{cc}
\cos (\theta) & -\sin (\theta)\\
\sin ( \theta) & \cos ( \theta)
\end{array} \right)=$ RHS. So statement holds for $n=1$.
Step 2: Inductive Assumption: Assume statement is true for $n=k$ such that
$\left(\begin{array}{cc}
\cos \theta & -\sin \theta \\
\sin \theta & \cos \theta
\end{array} \right)^{n}$
$=\left(\begin{array}{cc}
\cos \theta & -\sin \theta \\
\sin \theta & \cos \theta
\end{array} \right)^{k}$
$=\left(\begin{array}{cc}
\cos (k \theta) & -\sin (k\theta)\\
\sin (k \theta) & \cos (k \theta)
\end{array} \right)\etiqueta{1}$
Step 3: Prove Statement holds for $n=k+1$ such that
$\left(\begin{array}{cc}
\cos \theta & -\sin \theta \\
\sin \theta & \cos \theta
\end{array} \right)^{n}$
$=\left(\begin{array}{cc}
\cos \theta & -\sin \theta \\
\sin \theta & \cos \theta
\end{array} \right)^{k+1}$
$=\a la izquierda(\begin{array}{cc}
\cos \theta & -\sin \theta \\
\sin \theta & \cos \theta
\end{array} \right)^{k}$ $\times
\left(\begin{array}{cc}
\cos \theta & -\sin \theta \\
\sin \theta & \cos \theta
\end{array} \right)^{1}$
$=\a la izquierda(\begin{array}{cc}
\cos (k \theta) & -\sin (k\theta)\\
\sin (k \theta) & \cos (k \theta)
\end{array} \right)
\times
\left(\begin{array}{cc}
\cos \theta & -\sin \theta \\
\sin \theta & \cos \theta
\end{array} \right)$
[el uso de nuestra suposición inductiva $(1)$]
$=\left(\begin{array}{cc}
\cos\theta\cos (k \theta)-\sin\theta \sin(k\theta) & -\left(\sin \theta\cos (k \theta)+\sin (k \theta)\cos \theta\right)\\
\cos\theta\sin (k \theta)+\sin\theta \cos(k\theta) & \cos\theta\cos (k \theta)-\sin\theta \sin(k\theta)
\end{array} \right)$
$=\color{blue}{\left(\begin{array}{cc}
\cos (\theta(k+1)) & -\sin (\theta(k+1))\\
\sin (\theta(k+1)) & \cos(\theta(k+1))
\end{array} \right)}$
Where in the last step I used the fact that $$\cos(A \mp B)=\cos A \cos B \pm \sin A \sin B$$ and $$\sin(A \pm B)=\sin A \cos B \pm \cos A \sin B$$ and $\color{blue}{\mathrm{esta}}$ is the same result if $n=k+1$ es sustituido en el lado derecho de su disposición original.
De ahí la afirmación es verdadera para todos los $n \in \mathbb{N}.$
QED.
Ejemplo 3:
Demostrar por inducción que $3^{(3n+4)} + 7^{(2n+1)}$ es divisible por $11$ para todos los números naturales $n$:
Paso 1: Caso Base: para $n=1$: $P(1)= 3^{(3(1)+4)} + 7^{(2(1)+1)} = 2530$, que es divisible por $11$ tal declaración tiene por $n=1$.
Paso 2: Inductivo Asunción: Asumir la afirmación es verdadera para $n=k$: $P(k) =3^{(3k+4)} + 7^{(2k+1)} = 11a \implies 3^{3k+4} = \color{blue}{11a - 7^{2k+1}}$, donde $a \in \mathbb{N}$
Paso 3: Probar la Declaración tiene por $n=k+1$:
$P(k+1)= 3^{3k+7} + 7^{2k+3} = 27 \cdot 3^{3k+4} + 49\cdot 7^{2k+1}\tag{1}$
El uso de la suposición inductiva se muestra en la $\color{blue}{\mathrm{blue}}$, $(1)$ se convierte en:
$27(\color{blue}{11a - 7^{2k+1}})+49\cdot 7^{2k+1}=27\cdot 11a -27\cdot 7^{2k+1}+ 49\cdot 7^{2k+1}=27\cdot 11a +2\cdot 11\cdot 7^{2k+1}=\color{red}{11}(27a+2\cdot 7^{2k+1})$
Por lo tanto $3^{3n+4} + 7^{2n+1}$ es un múltiplo de a $\color{red}{11} \space\forall \space n\in \mathbb{N}$
QED.
Ejemplo 4:
Demostrar por inducción que $$\sum_{i=1}^n i^2 = \frac{n(n+1)(2n+1)}{6} \quad \forall \space n \in \mathbb{N}$$
Step 1: Basis Case: For $yo=1$: $$\sum^{i=k}_{i=1} i^2=\frac{1(1+1)(2\times 1+1)}{6}= \frac{2\times 3}{6}=1$$ So statement holds for $i=1$.
Step 2: Inductive Assumption: Assume statement is true for $i=k$:
$$\sum^{i=k}_{i=1} i^2=\frac{k(k+1)(2k+1)}{6} $$
Step 3: Prove Statement holds for $i=k+1$. You need to prove that for $i=k+1$: $$\sum^{i=k+1}_{i=1} i^2=\color{blue}{\frac{(k+1)(k+2)(2k+3)}{6}}$$
To do this you cannot use: $$\sum^{i=k}_{i=n} i^2=\color{red}{\frac{n(n+1)(2n+1)}{6}} $$ como este es lo que usted está tratando de demostrar.
Entonces, ¿qué puedes hacer en su lugar es un aviso de que:
$$\sum^{i=k+1}_{i=1} i^2= \underbrace{\frac{k(k+1)(2k+1)}{6}}_{\text{sum of k terms}} + \underbrace{(k+1)^2}_{\text{(k+1)th term}}$$
$$\sum^{i=k+1}_{i=1} i^2= \frac{k(k+1)(2k+1)}{6}+\frac{6(k+1)^2}{6}$$
$$\sum^{i=k+1}_{i=1} i^2= \frac{(k+1)\left(k(2k+1)+6(k+1)\right)}{6}$$
$$\sum^{i=k+1}_{i=1} i^2= \frac{(k+1)(2k^2+\color{green}{7k}+6)}{6}=\frac{(k+1)(2k^2+\color{green}{4k+3k}+6)}{6}=\frac{(k+1)\left(2k(k+2)+3(k+2)\right)}{6}=\color{blue}{\frac{(k+1)(k+2)(2k+3)}{6}}\quad \forall \space k,n \in \mathbb{N} \quad\fbox{}$$
Which is the relation we set out to prove. So the method is to substitute $i=k+1$ into the formula you are trying to prove and then use the inductive assumption to recover the $\color{blue}{\mathrm{blue}}$ equation at the end.
Observe that in the part marked $\color{green}{\mathrm{green}}$ $7k$ has simply been rewritten as $4k+3k$. From then on you simply take out common factors.
Note that this method is only valid when you have two numbers whose product is $12$ and sum is $7$.
Or, put in another way for the general quadratic $ax^2 +bx +c$, this inspection method is only valid iff you can find two numbers whose product is $ca$ and sum is $b$.